2018
DOI: 10.1108/bfj-02-2018-0098
|View full text |Cite
|
Sign up to set email alerts
|

Consumer segmentation based on health-related motive orientations and fruit and vegetable consumption

Abstract: Purpose More tailored interventions and campaigns are needed to increase fruit and vegetable consumption to recommended levels. The purpose of this paper is to explore which consumer groups exist based on both their fruit and vegetable consumption level and their health-related motive orientations (HRMO), and to compare the revealed consumer clusters regarding their fruit and vegetable product attribute importance. Design/methodology/approach In the Netherlands an online panel survey was carried out resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…In accordance with the studies by Geeroms et al (2008b) and Raaijmakers et al (2018). this study showed that health is a construct comprising multiple psychosocial dimensions that are weighted differently between consumers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In accordance with the studies by Geeroms et al (2008b) and Raaijmakers et al (2018). this study showed that health is a construct comprising multiple psychosocial dimensions that are weighted differently between consumers.…”
Section: Discussionsupporting
confidence: 89%
“…The results revealed a six-factor solution in line with a previous Dutch study (Raaijmakers et al, 2018). Within the current study, nine items were deleted, because their factor loadings were too low (o0.55) (Osborn et al, 2008) and five items were deleted because they loaded on a different dimension than expected based on Raaijmakers et al (2018). The remaining factors included the individualistic oriented motives "achievement", "active", "well-being", and "appearance", and the altruistic oriented motives "caring" and "social" (see Table I).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Demographic variables can act as a further sanity check: if seatbelt use rises with age, that variable should also follow a similar distribution in the health lifestyle clusters (i.e., more older people would be expected in more health-oriented clusters). As another example, interventions campaigns focusing on alcohol abuse in the US might use smoking as an outcome measure correlated with heavy drinking [22,23].…”
Section: Discussionmentioning
confidence: 99%